Urgency of Strengthening the Supervisory Function of the Broadcasting Commission in The Era of Media Disruption - Edi Pranoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Broadcasting Law is seen as less relevant to the development of broadcasting technology. The development of internet media content cannot be monitored by the Broadcasting Commission because the definition of broadcasting is only limited to television and radio. Meanwhile, there is no regulation that provides adequate regulation. In fact, the state must guarantee the delivery of healthy broadcasts to the public. The urgent revision of the Broadcasting Law is carried out by giving the Broadcasting Commission a broader supervisory authority, in order to ensure the fulfillment of the rights of the public to obtain proper broadcasts.